Antenna Array Performance with Number of Elements for Aperture Distributions. Issue 6 (1st November 2016) - Singh, Bharati; Sarwade, Nisha; Ray, K. P.
ABSTRACT: The main feature of an antenna array is its ability to form and scan the shaped main beam by using the amplitude and phase inputs as the controlling parameters at element level. In this paper, a comprehensive analysis of various parameters of a uniformly spaced linear array with respect to a number of elements for different amplitude distribution/window functions has been presented. There is a general assumption that any given window function will realize the expected parameters of the array even for a small number of array elements. A systematic study has been done to bring out very clearly the minimum number of elements that is required to realize antenna performance for a particular amplitude distribution. Effect of number of elements to obtain the desired first side lobe level and efficiency is presented. Contributions have been made to discuss the effects on directivity, gain, and beamwidth of the linear array.